A prospective population-based study of stroke in the Central Region of Iran: The Qom Incidence of Stroke Study. Issue 9 (October 2022) - Aghaali, Mohammad; Yoosefee, Sadegh; Hejazi, Seyed Amir; Shuaib, Ashfaq; Rahimi, Maryam; Razavinia, Fatemeh Sadat; Radmard, Fatemeh; Sabokbar, Tayebeh; Sharifipour, Ehsan
Objective: Based on the few population-based studies that have been conducted in the Middle East, we determined the incidence of stroke in Qom, one of the central provinces of Iran. Methods: The Qom province includes an estimated at-risk population of about 1 million. During a 12-month period (November 2018–November 2019), all first-ever strokes occurring in the target population were registered. Hospitalized cases were ascertained by discharge codes. Out-of-hospital cases were ascertained by a prospective screening of emergency medical services, emergency departments, ambulances records, primary care clinics, rural and urban public health centers, primary care physician offices, and neurologists' offices. Crude and age-adjusted incidence rates (per 100, 000 person-years) were calculated. Results: During the study period, 1462 first-ever strokes occurred with a mean age of 68.1 (17–103) years; of these 45.2% were females (661 cases). The crude annual incidence rate per 100, 000 at-risk populations was 145.4 (95% confidence interval, 138.1–153.0) for all types of stroke (156.5 for males and 134.3 for females), 26.4 (95% confidence interval, 23.5–29.8) for hemorrhagic stroke, and 114 (95% confidence interval, 105–121) for ischemic stroke. The incidence rate adjusted to the world population was 201.4 (95% confidence interval, 193–210) per 100, 000 at-risk populations (adj incidence, 218.5 for males vs 187.4 for females). The total fatality rate during the first 28 days was 19.6%. Conclusion: This study states that in this region there is a high incidence of stroke, which occurs at a younger age than the global average. There was a high prevalence of underlying stroke risk factors.